Strategies To Increase The Competence Of School Supervisors In The Department Of Education Implementation Unit (UPTD) II In Peudada District, Regency Bireuen - Rusdiman AB; M.Joharis Lubis; Sukarman Purba; Sri Milfayetti (CV. AFDIFAL MAJU BERKAH, 2022)
Key success something school very influenced by quality supervision education. Competence supervisor is wrong one factor enhancement quality education. Study this describe the strategy for increasing the competence of school supervisors at the Service Implementing Unit (UPTD)-II Education in Subdistrict Peudada Bireuen Regency. Study this use method descriptive with approach qualitative, technique collection data done through observation, interviews, and documentation. The research subject is the Head of UPTD, Coordinator Supervisor School, and Head of Division. Build Program. Results study show that: (1) Program enhancement competence supervisor school arranged by Head of Division. Build Program which implemented before teachings new month June until with month July with activity program including: determination of materials, methods, INSTRUMENTS, and stages for the supervisory recruitment activity plan schools, providing an understanding to supervisors regarding the procedures for implementing academic supervision and managerial, involving supervisors in training/upgrading, further education, competitions supervisor school achievers documented. (2) Implementation enhancement competence supervisor Schools that have been carried out, among others, carry out direct coaching in collaboration with the Department of Education and Culture Education and KORWASDA, select prospective school supervisors in accordance with applicable regulations applicable, involving supervisors in various training/upgrading activities and workshops. (3) Evaluation success enhancement competence supervisor school not yet own INSTRUMENT valid success. Assessment of program success is only carried out based on estimates very abstract. (4) Obstacles experienced in efforts to improve the competence of school supervisors include: other reasons are limited costs, limited human resources for trainers/instructors, and limited opportunities training / upgrading